Simultaneous double side grinding of silicon wafers: a review and analysis of experimental investigations - Qin, Na; Pei, Zhijian J.; Fisher, Graham R.; Liu, J. (My University, 2009)
Simultaneous double side grinding (SDSG) has become an important flattening process for manufacturing of 300 mm silicon wafers. However, the literature contains only a small number of papers on SDSG. In contrast, there are a large number of patents pertinent to this process. There is no review paper summarizing all these reported experimental results. This paper reviews the literature on experimental investigations on SDSG of silicon wafers. It first describes input variables in SDSG, and then presents their effects on output variables, covering warp, flatness, surface roughness, nanotopography, wafer-thickness variation, rotational asymmetry, grinding marks, subsurface damage, wheel wear, and process cycle time. It also discusses the definition,significance, and measurement of each of these output variables. Finally, it tabulates reported experiments to show what has and has not been reported in the literature.
Keywords: Flatness; Grinding; Nanotopography; Silicon wafer; Simultaneous double side grinding; Warp